Water masses, ocean fronts, and the structure of Antarctic seabird communities: Putting the eastern Bellingshausen Sea in perspective - Ribic, CA; Ainley, DG; Ford, RG; Fraser, WR; Tynan, CT; Woehler, E (2011)
Waters off the western Antarctic Peninsula (i.e., the eastern Bellingshausen Sea) are unusually complex owing to the convergence of several major fronts. Determining the relative inﬂuence of fronts on occurrence patterns of top-trophic species in that area, therefore, has been challenging. In one of the few ocean-wide seabird data syntheses, in this case for the Southern Ocean, we analyzed ample, previously collected cruise data, Antarctic-wide, to determine seabird species assemblages and quantitative relation- ships to fronts as a way to provide context to the long-term Palmer LTER and the winter Southern Ocean GLOBEC studies in the eastern Bellingshausen Sea. Fronts investigated during both winter (April– September) and summer (October–March) were the southern boundary of the Antarctic Circumpolar Current (ACC), which separates the High Antarctic from the Low Antarctic water mass, and within which are embedded the marginal ice zone and Antarctic Shelf Break Front; and the Antarctic Polar Front, which separates the Low Antarctic and the Subantarctic water masses. We used clustering to determine species’ groupings with water masses, and generalized additive models to relate species’ densities, biomass and diversity to distance to respective fronts. Antarctic-wide, in both periods, highest seabird densities and lowest species diversity were found in the High Antarctic water mass. In the eastern Bellingshausen, seabird density in the High Antarctic water mass was lower (as low as half that of winter) than found in other Antarctic regions. During winter, Antarctic-wide, two signiﬁcant species groups were evident: one dominated by Ade´ lie penguins (Pygoscelis adeliae) (High Antarctic water mass) and the other by petrels and prions (no differentiation among water masses); in eastern Bellingshausen waters during winter, the one signiﬁcant species group was composed of species from both Antarctic-wide groups. In summer, Antarctic- wide, a High Antarctic group dominated by Ade´ lie penguins, a Low Antarctic group ...